When ambition checks ambition: bureaucratic trustees and the separation of powers - Knott, Jack H.; Miller, Gary J. (2008)
A credible commitment to property rights and contract enforcement contributes to sustained economic growth. Credible commitment suffers when private interests collude with government to secure private gain over the public interest. The Madisonian separation of powers system was designed to hinder this kind of private gain by political factions. In this article, the authors ask what role public agencies play in promoting credible commitment, arguing that principal-agency theory is suspect from the Federalist viewpoint, which assumed that elected officials are self-serving in ways that can harm the public good. they offer an alternative approach called trustee theory. Trustees sometimes can best serve principals by not being responsive to the principals' interests, especially when the principals' pursuit of self-interest threatens the public interest in the long run. The authors then discuss constraints that limit trustee discretion, so that they themselves do not become a primary cause of weakened credible commitment. - Reproduced.
Keywords: Seperation of powers; Public administration